2022
DOI: 10.1021/jacsau.2c00248
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Mechanism of the Nonheme Iron Endoperoxidase FtmOx1 Using Substrate Analogues

Abstract: FtmOx1 is a nonheme iron (NHFe) endoperoxidase, catalyzing three disparate reactions, endoperoxidation, alcohol dehydrogenation, and dealkylation, under in vitro conditions; the diversity complicates its mechanistic studies. In this study, we use two substrate analogues to simplify the FtmOx1-catalyzed reaction to either a dealkylation or an alcohol dehydrogenation reaction for structure–function relationship analysis to address two key FtmOx1 mechanistic questions: (1) Y224 flipping in the proposed COX-like m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(48 citation statements)
references
References 70 publications
2
45
1
Order By: Relevance
“… Accordingly, NvfI introduces three oxygen atoms in one catalytic cycle of the nonheme iron enzyme. This feature of the NvfI reaction is different from the reaction of the previously characterized Fe­(II)/αKG-dependent fumitremorgin B endoperoxidase FtmOx1, which only installs the endoperoxide group without forming an additional hydroxyl group. Furthermore, assays using 18 O 2 and H 2 18 O suggested that the two oxygen atoms in the endoperoxide are derived from molecular oxygen while the oxygen atom in the hydroxyl group is derived from water, indicating that solvent exchange processes occur during the NvfI reaction.…”
Section: Mononuclear Nonheme Iron Enzymesmentioning
confidence: 63%
See 2 more Smart Citations
“… Accordingly, NvfI introduces three oxygen atoms in one catalytic cycle of the nonheme iron enzyme. This feature of the NvfI reaction is different from the reaction of the previously characterized Fe­(II)/αKG-dependent fumitremorgin B endoperoxidase FtmOx1, which only installs the endoperoxide group without forming an additional hydroxyl group. Furthermore, assays using 18 O 2 and H 2 18 O suggested that the two oxygen atoms in the endoperoxide are derived from molecular oxygen while the oxygen atom in the hydroxyl group is derived from water, indicating that solvent exchange processes occur during the NvfI reaction.…”
Section: Mononuclear Nonheme Iron Enzymesmentioning
confidence: 63%
“…Alternatively, the hydroxylation could occur via the hydrolysis of 60 , a hypothetical carbocation intermediate. In the related reaction of FtmOx1, the active site tyrosine residues Tyr224 and Tyr68 have been proposed to play key roles in H atom abstraction from the substrate or H atom donation to the radical intermediate. , However, the substitution of the active side tyrosine residue in NvfI did not abolish the endoperoxide activity of this enzyme. Thus, NvfI likely uses a strategy different from that of FtmOx1 to perform the iron-dependent endoperoxidation reaction …”
Section: Mononuclear Nonheme Iron Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…76 Liu and coworkers further argued that the COX-like mechanism is more feasible. 77 FtmOx1 is a tri-functional enzymes with endoperoxidation, alcohol dehydrogenation and dealkylation activities, which complicates mechanism investigation. By designing and synthesis of a substrate analogue, 13-oxofumitremorgin, and use it for crystallization and reaction, they can decouple the activities of FtmOx1 and showed structures and reactions that support rotation of Y224 during the reaction, favouring the original COX-like mechanism.…”
Section: Rsc Chemical Biology Papermentioning
confidence: 99%
“…Buffer exchange with HEPES solvent or removal of L-ascorbate both resulted in no reaction. While Liu and co-workers have reported that the absence of L-ascorbate and the use of stoichiometric enzyme results in direct oxidation of fumitremorgin B to 13-oxoverruculogen, 24 13-epi-fumitremorgin B did not react in the absence of L-ascorbate with aerobically purified protein. Contrary to our work, their preparation of FtmOx1 was under strictly anaerobic conditions, and their reaction used EDTA treated protein without a hexahistidine tag.…”
mentioning
confidence: 97%